PRMT5 control of cGAS/STING and NLRC5 pathways defines melanoma response to antitumor immunity - Kim, Hyungsoo; Kim, Heejung; Feng, Yongmei; Li, Yan; Tamiya, Hironari; Tocci, Stefania; Ronai, Ze'ev A (Science translational medicine, 2020)
Protein arginine methyltransferase 5 (PRMT5) controls diverse cellular processes and is implicated in cancer development and progression. Here, we report an inverse correlation between PRMT5 function and antitumor immunity. expression was associated with an antitumor immune gene signature in human melanoma tissue. Reducing PRMT5 activity antagonized melanoma growth in immunocompetent but not immunocompromised mice. PRMT5 methylation of IFI16 [interferon-γ (IFN-γ)-inducible protein 16] or its murine homolog IFI204, which are components of the cGAS/STING (stimulator of IFN genes) pathway, attenuated cytosolic DNA-induced IFN and chemokine expression in melanoma cells. PRMT5 also inhibited transcription of the gene encoding NLRC5 (nucleotide-binding oligomerization domain-like receptor family caspase recruitment domain containing 5), a protein that promotes the expression of genes implicated in major histocompatibility complex class I (MHCI) antigen presentation. PRMT5 knockdown augmented IFN and chemokine production and increased MHCI abundance in melanoma. Increased expression of and was associated with decreased melanoma growth in murine models, and increased expression of and correlated with prolonged survival of patients with melanoma. Combination of pharmacological (GSK3326595) or genetic (shRNA) inhibition of PRMT5 with immune checkpoint therapy limited growth of murine melanoma tumors (B16F10 and YUMM1.7) and enhanced therapeutic efficacy, compared with the effect of either treatment alone. Overall, our findings provide a rationale to test PRMT5 inhibitors in immunotherapy-based clinical trials as a means to enhance an antitumor immune response.